'Bless, O Lord, This Fruit of the New Trees': Liturgy and Nature in England in the Central Middle Ages*. (4th January 2016) - Rowe, Tamsin
Abstract : In Bede's dialogue on the book of Genesis, a pupil asks his master, 'Why did [God] bless man and the animals, but not the trees or the plants?' And the master replies: 'He blessed these things in order to increase their generation. [But] trees do not have the sense of perceiving or understanding … Therefore he did not say to the trees: Come forth and multiply.' This dialogue raises important issues about the benediction of different elements of the natural world. While God did not bless the trees and the plants at the Creation, nevertheless during Bede's time liturgical compilers were producing a body of material for just such a purpose. By the tenth century, benedictional texts for trees, fruits, nuts, seeds and herbs from different liturgical traditions were routinely included in the service-books of the western Church, petitioning God to multiply their number or else to bestow physical or spiritual well-being on those who used them.